Generative artificial intelligence in entrepreneurship education enhances entrepreneurial intention through self-efficacy and university support - Yingying Xie; Shaofeng Wang (Scientific Reports)
Abstract This study investigates how Generative Artificial Intelligence Supported Entrepreneurship Education (GAISEE) influences university students’ entrepreneurial intentions through a quantitative analysis of Chinese higher education institutions. Using structural equation modeling with data from 346 university students, we demonstrate that GAISEE significantly enhances both entrepreneurial self-efficacy (β = 0.523, p < 0.001) and entrepreneurial intention (β = 0.244, p < 0.001). The research reveals that entrepreneurial self-efficacy mediates the relationship between GAISEE and entrepreneurial intention, while the university entrepreneurial environment moderates these relationships. Notably, an optimized university environment strengthens the positive effects of GAISEE on both entrepreneurial self-efficacy (β = 0.333, p < 0.001) and entrepreneurial intention (β = 0.207, p < 0.001). These findings provide empirical evidence for the effectiveness of integrating generative AI technology in entrepreneurship education and highlight the importance of supportive university ecosystems in fostering student entrepreneurship.